Effect of different concentrations of serum supplementation on proliferation of embryonic cells derived from early stage in-vitro buffalo embryos - PURI, GOPAL; BAG, SADHAN; DAS, B C; ANEES, C; NATH, N C; MAJUMDAR, A C (The Indian Journal of Animal Sciences, 2010)
An attempt was made to study the effect of different culture condition on derivation of ES cell from IVF derived early stage embryos in buffalo. Early stage 16–32 cell stage IVF derived embryos were treated with proteinase-K for zona removal. The zona free embryos were cultured on mitomycin-c inactivated buffalo feeder cells in medium supplemented with different percentages of serum. It was observed that blastomere clump attached to the feeder cells within 24 h and multiplied. Supplementation of 20% FCS to the culture supplementation supported the multiplication of blastomere cells better than the supplementation of 10 or 15% serum. In some cases, there was formation of blastocyst like structure with distinct inner cell like mass although there were no trophectodermal cell at the border. When the inner cell like mass from the blastocyst like structure was cultured on inactivated feeder cells, no primary colony developed